Pembagian Harta Waris Menurut Hukum Adat Melayu Jambi Pada Kesatuan Masyarakat Adat Rumah Tuo Kec. Tabir Kab. Merangin - Kusuma, Agya; Oktaviarni, Firya (Zaaken: Journal of Civil and Business Law, 2023)
Jambi Malay customary law in the traditional community unit of the Rumah Tuo, Rantau Panjang village, Kec. Tabir Kab. Merangin and solving problems in the distribution of inheritance according to Jambi Malay customary law in the Unity of Indigenous Peoples of Rumah Tuo, Rantau Panjang Village, Kec. Tabir Kab. Merangin. The research method used is empirical juridical. The research specification is descriptive analytical, which provides an overview of the object under study. The results showed that the distribution of inheritance according to Jambi Malay customary law in the Tuo community unit, Rantau Panjang village was carried out on the principle of primacy, meaning that in receiving inheritance or accepting roles to manage inheritance, the levels of rights that caused one party to be more entitled than the other. another and the survivors who have the right are still there, the others have not received them. In the case of the problem of dividing the traditional inheritance of the Rumah tuo in Rantau Panjang Village, Tabir District, Merangin Regency, it is resolved by duduk basamo by means of (sitting together) with the principle of deliberation for the distribution of inheritance.